From ecology to engineering: the role of myxobacteria in recirculating aquaculture systems - Oskar Modin (Applied and Environmental Microbiology, 2025)
ABSTRACT Open microbial communities play vital roles in many engineered systems, providing essential ecosystem services but also posing operational challenges. In recirculating aquaculture systems (RASs), microbial activity is crucial for water purification, yet it can also lead to the accumulation of taste-and-odor compounds that compromise fish quality. In a recent study, Södergren et al. (Appl Environ Microbiol 91:e00757-25, 2025, https://doi.org/10.1128/aem.00757-25 ) report the first successful isolation of myxobacteria from RAS and demonstrate their ability to produce geosmin and other volatile organic compounds under various nutrient conditions, including in real RAS water. This work provides foundational insights into the ecological roles of myxobacteria and their contributions to off-flavor formation in aquaculture environments. In this commentary, I reflect on the broader significance of microbial ecology in environmental biotechnology and discuss how the findings of Södergren et al. may inform future strategies for managing microbial communities in RAS to improve system performance and product quality.